Phenotyping of productivity and resilience in sweetpotato under water stress through UAV-based multispectral and thermal imagery in Mozambique - Ramírez, D.; Grüneberg, W.J.; Andrade, M.I.; Boeck, B. de; Loayza, H.; Makunde, G.S.; Ninanya, J.; Rinza, J.; Heck, S.; Campos, Hugo (Wiley, 2023)
Sweetpotato is a crucial crop to guarantee food security in sub-Saharan Africa, and drought events are considered one of the most critical factors affecting sweetpotato productivity in this region. In this study, airborne imagery based on reflectance (NDVI, CIred-edge) and canopy temperature minus air temperature (dT) indices was used to characterize sweetpotato genotypes under drought treatments in Mozambique. Two field experiments established in rainy/hot (Trial A) and dry/cool (Trial B) seasons were assessed. In Trial A, 24 genotypes were subjected to early- (ESD), mid- (MSD) and late-season (LSD) drought stress treatments and compared against a control. In Trial B, 120 genotypes were subjected to LSD only. The percentage of reduction in vine weight (PRVW) under drought was related primarily to temporal variation of NDVI and CI, regardless of drought treatment and seasons. dT in relation to control (dTAmp) was associated with PRVW in ESD-Trial A and LSD-Trial B, whereas under LSD-Trial A, dTAmp was related to total fresh storage root weight (TRW). During the rainy/hot season, higher TRW reduction was promoted under ESD; however, under LSD, it was possible to identify productive genotypes able to withstand drought stress, highlighting their relevance for drought-tolerance selection purposes.